Spin-dependent quantum interference in photoemission process from spin-orbit coupled states - Koichiro Yaji (Nature Portfolio, 2017)
Spin–orbit coupling produces spin–orbital-entanglement in quasiparticle eigenstates. Here, Yajiet al. present a general description of spin–orbital-entangled states and establish a model for dipole transition based on spin-dependent quantum interference, that permits optical spin control.